Constraints and opportunities for groundwater irrigation arising from hydrologic shifts in the Iullemmeden Basin, South-Western Niger - Torou, Bio Mohamadou; Favreau, G.; Barbier, Bruno; Pavelic, Paul; Illou, Mahamadou; Sidibe, F. (Informa UK Limited, 2013)
Land-use-change-induced increases in shallow groundwater levels across parts of the Sahel in recent years have coincided with expanded use of groundwater for irrigation. This study was conducted to assess the potential linkages and livelihood implications based on a field survey of nine villages building on previous hydrological studies. The results show that irrigators lack effective means of production and mostly rely on manual methods. Borehole usage is more pro table and reliable than shallower wells. Overall incomes from irrigation are relatively small and severely constrained by the limited field scale due to high establishment and operating costs.